The Use of Natural Sorbents in Cow Feed to Reduce Gaseous Air Pollutants and Faecal Biogenic Compounds - Bożena Nowakowicz-Dębek; Łukasz Wlazło; Jolanta Król; Katarzyna Karpińska; Mateusz Ossowski; Hanna Bis-Wencel; Wojciech Ospałek (Animals)
The implementation of new technologies and best practices on factory farms is crucial for reducing the environmental pollution burden. This study aimed to evaluate the use of natural sorbents in the cows’ diet to reduce gaseous pollutants released on the farm and the content of faecal biogenic compounds. To this end, a mixture of natural sorbents (65% beechwood biochar, 25% aluminosilicate, and 10% glycerine) was added to cows’ feed. Pollutants released from all groups of cows were continually monitored on the farm during the experiment. Blood samples were also collected from the cows for haematological and biochemical analysis to determine the sorbents’ impact on their health. The average level of gaseous pollutants in the air on the farm were highest in the control group and lowest in the experimental groups. The levels of NH3, CH4, and H2S were statistically significant at p < 0.05. The results demonstrated that the added sorbents effectively reduced gaseous pollutants without adversely affecting the health of cows. Natural additives in the cows’ diet, including sorbents, bind harmful substances such as NH3 and CH4, which are common gaseous by-products of digestion. This leads to improvements in animal welfare and the natural environment.